Educação em administração à luz da teoria crítica em Theodor Adorno: um estudo fenomenográfico sobre a emancipação na graduação - Santos, Anderson dos (2025)
For Adorno, education is essential in the formation of emancipated individuals beyond the transmission of knowledge decontextualized from social practice. For this reason, the relevance of this study lies in the need to rethink Management Education (ME), which is often limited to technical and standardized knowledge, without considering the formation of critical professionals who are aware of their social role. This dissertation aims to understand how Adorno's Critical Theory manifests itself in Management Education from the perspective of the emancipation of undergraduate students. This study seeks to explore the interconnections between critical theory and emancipation in ME, promoting a discussion about the training of professionals who not only master administrative techniques but are also capable of questioning, reflecting, and acting ethically and responsibly in their practices. Methodologically, as a theoretical lens, we adopt critical theory and the radical humanist paradigm. As for the nature of the research, we employed a qualitative research approach, using the phenomenography method to deepen our understanding of the phenomenon of ME based on the students' experiences. The research was conducted through semi-structured interviews and document analysis, whose data were examined using the phenomenographic method and narrative analysis. ATLAS.ti software was used to facilitate the identification of patterns and thematic categories that emerged from the students' narratives. The main results highlight the importance of incorporating Critical Theory and the emancipatory approach into the curriculum and pedagogical practices of Management courses, promoting critical thinking, autonomy, and student leadership from the beginning of their education. In addition, the research highlights the disparity between normative guidelines and the practical effectiveness of these proposals, suggesting the need for improvements in the curriculum structure and continuing education of the teaching staff. Finally, the results point to the relevance of active methodologies, research and extension projects, and the strengthening of the dialogue between theory and practice, aiming to expand the social impact of business education. Thus, we have chosen as contributions of the research the interrelationships between the findings of the study, which contribute to the advancement of academic knowledge in ME, with an emphasis on emancipation; encouraging the use of creative teaching methods and the inclusion of critical studies in teaching practice in Management; in addition to presenting the sociopractical contributions resulting from the study for students, the university, and society. In this dissertation, we propose a critical reflection on ME, contributing to social transformation, in which student emancipation becomes imperative for the construction of a critical spirit about reality and, consequently, for a more responsive society.